Intrathecal Magnesium Sulfate as Analgesic and Anaesthetic Adjunct to Bupivacaine in Patients Undergoing Lower Extremity Orthopaedic Surgery - Limbu, Prakash Maden; Khatiwada, Sindhu; Sah, Birendra Prasad; Singh, Satyendra Narayan; Pokharel, Krishna; Maharjan, Rajiv (Journal of Society of Anesthesiologists of Nepal, 2018)
Background: Subarachnoid block is a popular mode of anesthesia for lower limb surgeries. Studies of Magnesium Sulfate (MgS04 ) as an adjuvant to intrathecal local anaesthetic are limited. The objective was to find out the analgesic and anaesthetic effect of intrathecal MgS04 added to bupivacaine for spinal anaesthesia in patients undergoing lower extremity orthopaedic surgery. Methods: Sixty ASA I or II adult patients undergoing lower extremity orthopaedic surgery were randomly allocated in a double blinded fashion into two groups of thirty each. Group A received 3.0 ml of 0.5% hyperbaric bupivacaine with 0.15 ml of 50% MgSO4. Group B received 3.0 ml of 0.5% hyperbaric bupivacaine with 0.15 ml of NS. Onset of sensory and motor block as well as time to attain highest level of sensory block were recorded. Duration of sensory and motor block along with duration of spinal anaesthesia were also assessed. Any adverse effects were noted and treated. Results: Duration of sensory and motor block along with duration of spinal anaesthesia were prolonged in patients of MgSO4 but were not statistically significant with p-value of 0.33, 0.23 and 0.68 respectively. Onset of anaesthesia, requirement of rescue analgesics, haemodynamic parameters and adverse effects were comparable between two groups. Conclusion: In patients undergoing lower extremity orthopaedic surgery the addition of 75mg of MgSO4 to intrathecal bupivacaine did not prolong the duration of sensory block, spinal anaesthesia nor decreased postoperative analgesic consumption without any additional side effects. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, Page: 74-80